The movement and distribution of pregnant spotted ragged-tooth sharks, Carcharias taurus, in the iSimangaliso Wetland Park, South Africa - Sara C. Cerqueira; Jennifer Margaret Olbers; Grant Smith; Michelle Carpenter; Mário J. Pereira; Geremy Cliff (PeerJ)
The spotted ragged-tooth shark, Carcharias taurus, is widely distributed in subtropical continental coastal seas. In South Africa, it is commonly found along the entire south and east coasts, including the iSimangaliso Wetland Park (IWP) in the far north, which is the largest Marine Protected Area on the South African coast. Pregnant females occur there for much of the year, with the largest aggregations in summer. It is here we used remote underwater photography (RUP), supplemented with in-situ surveys to photo-identify individuals, using unique spot patterns. Three known aggregation sites (Raggie Reef, Quarter-Mile Reef and Mushroom Rocks) were monitored over a 5-year period between 2018 and 2023. We photo-identified 574 individuals (569 females and five males) and registered 1,200 sightings, using images of the right flank. The identification of new individuals persisted throughout the study, with the discovery curve showing no signs of reaching an asymptote. A total of 97% (n = 550) of females observed were noticeably pregnant. Individuals were consistently identified across all sample years and at all three reefs, exhibiting movements among the three monitored sites. The reproductive cycle is generally regarded as 2 years, but some females appeared to have a 2-year rest between pregnancies. Raggie Reef, which lies in the sanctuary zone, emerged as the reef with the highest index of popularity, as individuals were present almost constantly (90% of the sampling days). The findings of this study confirm the crucial role that the IWP plays in the conservation of a species that is globally Critically Endangered.